Addressing Climate Change Communication: Effective Engagement of Populations for Climate Action in the US and Globally - Ana Viamonte Ros; Regina LaRocque; Rachel Fortinsky; Patrice Nicholas (Ubiquity Press, 2020)
Background: Communication about climate change is critical in addressing the greatest public health challenge of our time. Public health professionals must convey the human implications of climate change and educating populations regarding climate change as a threat to the health and wellbeing of people globally. Effective communication to engage individuals, communities, and populations is critical to debate as we focus on the most urgent public health problem of our time. Objective: Public health professionals are aware of the deleterious health consequences related to climate change; however, key segments of the population are not. This paper addressed key concepts related to climate change communication. Methods: Databases were searched including PubMed, CINAHL, and Scopus from 2015 to 2020 to obtain the most recent relevant literature using search terms that included climate change, climate communication, climate action, and climate change engagement. Findings: Climate change communication as viewed through the lens of Six Americas-a national survey that categorized people regarding their beliefs about climate change from those who are Dismissive, Doubtful, Disengaged, Cautious, Concerned, or Alarmed is a valid perspective for engaging populations in climate communication and climate action. Conclusions: Using the framework developed by the George Mason University Center for Climate Change Communication and the Yale Program on Climate Change Communication, we suggest that adopting this framework from a US perspective to a global perspective and surveying across countries and context is imperative to advance global understanding of the impact of climate change on health.